Traditional Chinese Medicine: A promising strategy to regulate inflammation, intestinal disorders and impaired immune function due to sepsis - Wang, Xu-Hua; Xu, Ding-Qiao; Chen, Yan-Yan; Yue, Shi-Jun; Fu, Rui-Jia; Huang, Lu; Tang, Yu-Ping (Frontiers in Pharmacology, 2022)
GRAPHICAL ABSTRACT